Kultur Massal dalam Bentuk Alami Maupun Konsentrat [Massal Culture of Scenedesmus Sp. As An Effoct to Get Rotifera Feed In Natural and Concentrate ] - Sri Cahyaningsih; Slamet Subyakto (Jurnal Ilmiah Perikanan dan Kelautan, 2009)
AbstractScenedesmus sp. is a microalgae as a fish and shrimp larva feed because the high nutrition value, easy to culture and harvest. The aim of these research are to know massal culture of the high density of Scenedesmus sp. and to use for Rotifera feed (natural and concetrate type). 3The experiment used one m of massal culture of Scenedesmus sp. In 0,8,16 and 24 ppt. The result showed 6that 16 ppt treatment gave the best daily growth of Scenedesmus sp.(6.78 x 10 cell/ml). Analysis of proximate and fatty acids of Scenedesmus sp. In 16 ppt also showed the best contents of protein, fat, EPA and DHA.